Valproic acid has neuroprotective effect in an acute model of oxidative stress in rats (Gaceta de Ciencias Veterinarias, 2015)
The excess of the free radical production at has been implied has a common factor in pathogenesis of a big number of neurodegenerative processes, including Alzheimer’s and Parkinson’s disease and in ischemia/reperfusion induced brain damage. Valproic Acid (VPA), which traditionally has been used as an antiepileptic drug, now is proposed as a neuroprotective agent, but is not clear it’s mechanisms of action. In this paper, its effect was investigated in an acute oxidative stress model with Sprague Dawley rats, in which iron sulfate was used as injury and lipid peroxidation and carbonylated proteins were quantified at cerebral cortex, showing that it blocked formation of free radicals. Levels of MDA atcerebral cortex that received oxidative injury in the group of animals treated with VPA were 57% lower in comparison to control group, also the amount of carbonylated proteins was 65% lower in the cerebral cortex of experimental animals in contrast to control group. Furthermore, it was found that the antioxidant effect showed by the VPA, was equally significant than showed by vitamin E.
Keywords: valproic acid; free radicals; cerebral cortex; neuroprotection